Pelatihan Strategi Branding dan Marketing Mix Produk Ecoenzym di Desa Landbaw Kecamatan Gisting Kabupaten Tanggamus - Citra Kunia Dewi; Faisal Abi; Ulil Albab; Nanda Alhusna; Rahma Aulia Nazwa (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Household waste has not been utilized properly and is generally considered as garbage. In fact, it can be utilized as an ecoenzyme organic fertilizer that is not only beneficial for the soil and plants themselves, but can also reduce household waste in the form of fruit and vegetable waste. In general, household waste in Landbaw Village, Gisting District, Tanggamus Regency has been utilized properly as organic fertilizer. However, it has not been optimal. This is due to the absence of branding and marketing itself in order to introduce and distribute it to the wider community. Therefore, community service activities were held in Landbaw Village, Gisting District, Tanggamus Regency through counseling on how to package a product to make it more attractive and make other people trust our products so as to increase income.